Regresi Logistik: Pengaruh Kualitas E-Learning Terhadap Keinginan Melanjutkan Penggunaan E-Learning Madrasah - Siska Merrydian; Awaluddin Tjalla; Mahdiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study intends to decide the impact of e-learning quality on the longing to keep utilizing e-learning of madrasah aliyah understudies. The number of inhabitants in this study is understudies of madrasah aliyah in DKI Jakarta area. Testing was completed by convinience inspecting and an example of 251 understudies was gotten. The information examination strategy utilizes straightforward calculated relapse. The outcomes showed that there was an impact of e-learning quality on the longing to keep utilizing e-learning; great nature of e-learning has a degree of readiness of understudies to keep utilizing e-advancing by multiple times higher than terrible nature of e-learning; and the likelihood of understudies needing to keep utilizing e-learning if the nature of e-learning is great is 0.675